QualiAB: desenvolvimento e validação de uma metodologia de avaliação de serviços de atenção básica QualiAB: development and validation of a methodology for the assessment of primary health care services - Elen Rose Lodeiro Castanheira; Maria Ines Battistella Nemes; Margareth Aparecida Santini de Almeida; Rodolfo Franco Puttini; Ivete Dalben Soares; Karina Pavão Patrício; Mariana Arantes Nasser; Dinair Ferreira Machado; Antonio Luís Caldas Junior; Roseli d'Avilla Vasconcelos; Stella Brasil Pissato; Josiane Fernandes Lozigia Carrapato; et al. (Universidade de São Paulo, 2011)
Este artigo apresenta o desenvolvimento, validação e utilização de uma metodologia de avaliação da qualidade dos serviços de atenção primária do Sistema Único de Saúde (SUS), o Questionário de Avaliação da Qualidade de Serviços de Atenção Básica (QualiAB). Destina-se aos serviços de atenção básica, organizados segundo diferentes modelos de atenção, incluindo a Saúde da Família. Contém 50 indicadores sobre oferta e organização do trabalho assistencial e programático e 15 sobre gerenciamento, na forma de questões de múltipla escolha, autorespondidas via web pela equipe local do serviço. Confere a cada resposta valor zero, um ou dois; a média geral atribui ao serviço um grau de qualidade expresso pela distância do melhor padrão correspondente à média dois. Foi construído por processo de consenso interativo, que incluiu metodologias qualitativas, teste-piloto, aplicação em 127 serviços, validação de construto e confiabilidade. Respondido, em 2007, por 598 (92%) dos serviços de 115 municípios paulistas, mostrou bom poder para discriminar níveis de qualidade. Adotado em 2010 como parte de um programa de apoio à Atenção Básica da Secretaria de Estado da Saúde de São Paulo, foi respondido por 95% (2.735) dos serviços de 586 municípios (90,8% do Estado). Os resultados foram encaminhados aos municípios. O QualiAB fornece uma avaliação válida, simples e com a possibilidade de retorno imediato para gerentes e profissionais. Mostrou factibilidade, aceitabilidade, bom poder de discriminação e utilidade para auxiliar a gestão da rede de atenção básica do SUS em São Paulo. A experiência indica aplicabilidade nas redes de atenção básica do Brasil. This paper presents the development, validation and utilization of a methodology for assessing the quality of the primary health care services of Sistema Único de Saúde (SUS - Brazil's National Health System), the Questionnaire for the Assessment of the Quality of Primary Health Care Services - QualiAB. It is addressed to all primary health care services, organized according to different care models, including Family Health. It contains 50 indicators about availability and organization of the care and programmatic work, and 15 about local management, in the form of multiple choice questions self-responded through the Web by the local service team. It attributes to every answer the values zero, one or two; the general average attributes a 'quality degree' to the service, expressed by the distance to the best standard corresponding to the average two. It was built by an interactive consensual process, which included qualitative methodologies, pilot-testing, application to 127 services, construct validation and reliability. It was answered in 2007 by 598 (92%) services of 115 municipalities of the State of São Paulo, showing good sensitivity to differentiate quality levels. It was adopted in 2010 as part of a supporting program to the Primary Health Care of São Paulo's State Health Department, being answered by 95% (2735) of the services of 586 cities (90,8% of the State). The results were sent to the municipalities. QualiAB provides a valid and simple assessment, with immediate feedback to managers and professionals. It has shown feasibility, acceptability, power to differentiate quality levels and utility to help the management of the primary health care network of SUS in São Paulo. This experience might be extended to Brazil as a whole.